TVET Professional Educator : Guidance on the competency development - Affero Ismail; Razali Hassan; Mohd Irman Harun (2020)
Technical and Vocational Education and Training (TVET) has stolen the limelight in education sector that it is very much sought after for economy growth of a country and the answer for the never-ending emplyability issue. The basic role of TVET was viewed as just a mere supplier of skilled labour. However, it has just made a turning point today as TVET has ascended to being a catalyst for economic and sustainable development. The challenge for a country is in ensuring that its human capital possesses the necessary attributes and qualities to be in rhythm with the needs of the ever-changing world. Towards this direction, we need to strengthen the TVET educator capabilities and to improve the educator’s programme implementation. Up-skilling and re-skilling programme for TVET Educator is essential in producing quality TVET graduates. Therefore, this book is designed and structured with important contents that would assist the TVET Educator in implementing self-reflection and evaluation as well as to be used the best reference with regard to TVET Educator training that will bring impact to the professional development and lifelong learning particularly for higher TVET level.